Study of the Ground-State Energies of Some Nuclei Using Hybrid Model - Hussien, R.; Sewailem, Sh. M.; Abou-Salem, L. I. (Advances in High Energy Physics, 2021)
The quark-quark (QQ) interaction as a perturbed term to the nucleon-nucleon interaction (NN) without any coupling between them is studied in a hybrid model. This model is used to calculate the ground-state energies of 2H1 and 4He2 nuclei. In a semirelativistic framework, this model is encouraged for light nuclei and the instanton-induced interaction by using the QQ potential and the NN interaction for a small scale around the hadron boundaries. This hybrid model depends on two theories, the one-boson exchange potential (OBEP) and the Cornell-dressed potential (CDP) for QQ. A small effect of quark-quark interaction is obtained on the values of the ground-state energies, around 6.7 and 1.2 percentage for 2H1 and 4He2, respectively nuclei.